Model Task Sharing dalam Community Based Healthcare: Studi Kasus pada Program SMART Health di Desa Sidorahayu Kecamatan Wagir Kabupaten Malang Jawa Timur - Sujarwoto, Sujarwoto (Jurnal Ilmiah Administrasi Publik, 2018)
This paper examines model of task sharing in community based healthcare within SMARThealth program in Sidorahayu village Malang East Java Indonesia. A single case study was applied to explore task sharing model from health workers to non health workers in health screening for risks of cardiovascular disease. Indepth interviews were conducted to 10 key informants between January to May 2018. The findings show that task sharing model occurs within a health facility in which non health workers can provide services with adequate competency and quality. Responsibilities in health screening is delegated to lower level health service providers so that it can effectively reach consumers. The results sugests that task sharing model provides an alternative model for solving low number and distribution of health workers in rural areas in providing health screening for cardiovascular risks.